Effects of Longitudinal Vibration on Hardness of the Weldments - Tewari, S.P.; Shanker, A. (My University, 1994)
The paper pertains to the effects of longitudinal vibration, frequency and amplitude on hardness of the weldments prepared by metal arc welding under dynamic conditions. The frequency range was 0 to 400 Hz and amplitude range was 0 to 40μm respectively. Investigations show that the hardness of the weldments have increased when compared with the stationary welded test specimens. 0 to 400 Hz frequency range and 5 to 20 μm amplitude range produce good results. © 1993, The Iron and Steel Institute of Japan. All rights reserved.
Keywords: amplitude; frequency; hardness; mild steel; stationary; vibratory; weld